2020
DOI: 10.1590/1678-4685-gmb-2019-0292
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of AtNCED3 gene improved drought tolerance in soybean in greenhouse and field conditions

Abstract: Water deficit is an important climatic problem that can impair agriculture yield and economy. Genetically modified soybean plants containing the AtNCED3 gene were obtained aiming drought-tolerance improvement. The NCED3 gene encodes a 9-cis-epoxycarotenoid dioxygenase (NCED, EC 1.13.11.51), an important enzyme in abscisic acid biosynthesis. ABA activates the expression of drought-responsive genes, in water-deficit conditions, targeting defense mechanisms and enabling plants to survive under low water availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 75 publications
2
13
0
Order By: Relevance
“…Previous studies evaluated the expression level of dehydrin in response to abiotic stresses and showed increased levels in response to osmotic stress (Chiappetta et al, 2015), ABA, salicylic acid, and methyl jasmonate application, and drought, cold and, heat stresses in grapevine (Yang et al 2012). Specifically, in soybean GM with different transcriptional factors, higher expression levels of LEA2 and LEA6 genes under WD were identified (Honna et al, 2016;Fuganti-Pagliarini et al, 2017;Molinari et al, 2020), corroborating the results obtained in the current study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies evaluated the expression level of dehydrin in response to abiotic stresses and showed increased levels in response to osmotic stress (Chiappetta et al, 2015), ABA, salicylic acid, and methyl jasmonate application, and drought, cold and, heat stresses in grapevine (Yang et al 2012). Specifically, in soybean GM with different transcriptional factors, higher expression levels of LEA2 and LEA6 genes under WD were identified (Honna et al, 2016;Fuganti-Pagliarini et al, 2017;Molinari et al, 2020), corroborating the results obtained in the current study.…”
Section: Resultssupporting
confidence: 90%
“…The mean length of internodes corresponded to the ratio between H1 and H2 and the number of nodes. The relative growth rate in height (RGRH) was calculated according to Molinari et al (2020). Total leaf area was measured using a leaf area meter (LI 3100C).…”
Section: Relative Growth Rate (Rgr) In Seedlings During Germination Growth Parameters and Physiological Responses In The Veg Periodmentioning
confidence: 99%
“…RD26A , COR47 , ERD4 , ERD9 , and ERD10 , the gene for a key-enzyme of ABA synthesis, NCED3 , appeared strongly induced in ami1-2 . The overexpression of NCED3 has recently been associated with an improvement of drought tolerance in soybean ( Molinari et al , 2020 ). Both the induction of NCED3 through IAM application and the accumulation of ABA in the ami1 alleles could be confirmed ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, serine protease inhibitors play an important role in cell survival, development, and host defense, i.e., transgenic Arabidopsis thaliana plants overexpressing serine protease inhibitors showed higher RWC, reduced lipid peroxidation, and enhanced activity of antioxidant glutathione-S-transferase [61]. This cluster also grouped four genes encoding the 9-cis-epoxycarotenoid dioxygenase (NCED), involved in ABA biosynthesis and related to dehydration stress tolerance in Arabidopsis [43,[62][63][64]. Interestingly, NCED genes showed higher FC values under mild-WS than in severe-WS, indicating that they are involved in the early response to water deficit.…”
Section: Validation Of the Microarraymentioning
confidence: 92%